2013
DOI: 10.1111/aji.12120
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Metallothionein Immunoreactivity in Stromal Fibroblasts and Macrophages in Cases of Uterine Cervical Carcinoma With Respect to Both the Local and Distant Spread of the Disease

Abstract: The level of MT immunoreactivity found in the fibroblasts and macrophages within the tumor microenvironment seems to be indicative of the intensity of the remodeled cervical tumor microenvironment, and this in turn may be related to the local advancement of the disease. Moreover, it appears that the intensity of the metallothionein immunoreactivity in the immunoreactivity profile of the cervical tumor may be linked to both the depth of the local invasion and the extent of the distant advancement of the disease. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…In the present study, MT immunoreactivity was also found to be expressed by the stromal fibroblasts. This correlates with the pattern of MT expression in other histological tumour types, such as adenocarcinomas and squamous cell carcinomas [22][23][24][25]. Stroma is tissue that undergoes intensive remodelling during tumour development, which is also induced by factors secreted from its own tumour cells [40].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the present study, MT immunoreactivity was also found to be expressed by the stromal fibroblasts. This correlates with the pattern of MT expression in other histological tumour types, such as adenocarcinomas and squamous cell carcinomas [22][23][24][25]. Stroma is tissue that undergoes intensive remodelling during tumour development, which is also induced by factors secreted from its own tumour cells [40].…”
Section: Discussionsupporting
confidence: 69%
“…In our previous studies, we demonstrated and analysed the involvement of the tumour microenvironment in the development of various types of malignant epithelial neoplasms. The microenvironment was associated with its own remodelling and the acquisition of a suppressive tumour microenvironment [22][23][24][25]. Additionally, we demonstrated the presence of tumour microenvironment remodelling with RCAS1 expression and RCAS1-positive macrophages in the tumour microenvironment of palatine tonsil DLBCL.…”
Section: Introductionmentioning
confidence: 59%
“…This fact can also be supported by the finding that fibroblasts exhibited high vimentin and MT immunoreactivity levels in the tumour microenvironment [19], which could be reason for the higher expression of MT in the tumour-adjacent tissues. Furthermore, the rate of MT protein expression in macrophages and fibroblasts in the tumour microenvironment appears to be an indicator of microenvironment remodelling associated with the local progression of cancer [25]. Higher MT expression was detected in the primary tumour itself than in its derived lymph node metastases [26].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells are not only responsible for the evasion of cancer cells from immune surveillance, but also cooperate with other immune cells, including TAMs, which are predominantly from M2 subgroups [29,30]. These subgroups are responsible for the secretion of TGF-beta and Il-10 that support the differentiation of Treg cells [31].…”
Section: Discussionmentioning
confidence: 99%